Exploring activity differences between the hydroformylation catalysts: Insights from theory - Dangat, Yuvraj B.; Rizvi, Masood Ahmad; Pandey, Pippalad; Vanka, Kumar (Journal of Organometallic Chemistry, 2016)
Hydroformylation catalysis is the most important homogeneous catalysis process of the current day. The current computational investigation aims to understand the nature of the hydroformylation process when monodentate ligands are employed. The complete catalytic cycle for different monodentate ligands bound to the rhodium center has been studied with full quantum chemical calculations, with density functional theory (DFT). To the best of our knowledge, this is the first systematic investigation of the relative free energy surfaces for mono-coordinate monodentate and bi-coordinated monodentate ligands in hydroformylation catalysis. The results indicate that the barriers are lower for the mono-coordinate monodentate species in comparison to the bi-coordinate monodentate, for all the ligand cases studied, indicating higher activity for the mono-coordinate monodentate active species. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Density functional theory (DFT) calculations; Hydroformylation; Monodentate; Rhodium